An Inventory Model Considering All Unit Discount and Carbon Emissions - Kristiyani, I.M.; Daryanto, Y. (Universitas Atma Jaya Yogyakarta, 2019)
Consumer satisfaction is an important factor in the ongoing business process. Companies must be able to meet consumer demands and considers customers’ concerns on price. In a supplier and customer relationship, a given discount will affect the order size. Besides, in the current developing industry, environmental factors must be considered without disturbing the business. Recently, researchers and practitioners develop environmentally-friendly industries so that the environment will be well managed and not polluted. For example, carbon emissions can be managed by optimizing the production operation and product distribution. This paper presents a study on the relationship between discount on the economic order quantity model and the total carbon emissions. This research develops a procurement model by considering an all-unit discount system and carbon emission tax. The aim is to determine the optimal order that minimizes the total cost.